Escape beam statistics and dynamical properties for a periodically corrugated waveguide - da Costa, Diogo Ricardo; Silva, Mário R.; Leonel, Edson D. (Elsevier, 2013)
Some escape and dynamical properties for a beam of light inside a corrugated waveguide are discussed by using Fresnel reflectance. The system is described by a mapping and is controlled by a parameter δ defining a transition from integrability (δ = 0) to non integrability (δ ≠ 0). The phase space is mixed containing periodic islands, chaotic seas and invariant tori. The histogram of escaping orbits is shown to be scaling invariant with respect to δ. The waveguide is immersed in a region with different refractive index. Different optical materials are used to overcame the results. © 2013 Elsevier B.V. All rights reserved.
Keywords: Corrugated waveguide; Escape properties; Fresnel